A simple process to achieve microchannels geometries able to produce hydrodynamic cavitation. (2nd March 2017) - Qiu, X; Cherief, W; Colombet, D; Ayela, F
Abstract: We present a simple process to perform microchannels in which cavitating two phase flows are easily producible. Up to now, hydrodynamic cavitation 'on a chip' was reached with small flow rates inside microchannels whose micromachining had involved a deep reactive ion etching (D-RIE). The process we present here does not require a D-RIE reactor, as it is only funded on a wet etching of silicon. It leads to a so-called microstep profile, and large cavitating flow rates become possible together with moderate pressure drops.